(untitled) (Raparin Journal of Humanities (RJH), 2021)
In this paper, we investigated changes in cold waves in Kurdistan region over the period 2000–2017. Cold waves it means decrease 5oc minimum temperature degree at least from the average monthly minimum temperature for this month and continues for 3 days consecutive at least. The study found 132 cold waves repeat in Kurdistan region, that is 112 waves were the type of shortwave it means %84.85 of them were shortwaves, 18 waves medium and only 2 waves were the type of long waves. About severity of the temperature of cold waves the study also, found different types, for example in all cold waves about %67.42 or 89 waves were from the type of moderate waves, 30 waves strong and 13 waves were extreme. About of the cold days over the period of time include 904 threshold cold waves, in this number 530 days were in the type of the cold day of cold waves, and 374 days were the Temperature fluctuation of cold days. As well as the paper found that the annual repetition cold waves vary from month to month, and the season to season, it was found that cold waves were highest in spring and lowest in summer. The most geographical distribution of system atmospheric pressure effect on the weather and cold waves in study area is The Siberian Heights.